913 Nanoparticle emission during cutting operation of carbon nanotube reinforced polycarbonate composites and recycling effect. (24th April 2018) - Boonruksa, Pongsit; Bello, Dhimiter; Isaacs, Jacqueline; Mead, Joey; Woskie, Susan
Abstract : Introduction: Carbon nanotubes (CNTs) are widely used as a nanofiller in polymer composites to improve the quality of neat polymers. However, the use of CNT are threatened by concerns over its toxicology. The purpose of this study was to investigate the potential emissions of NPs and CNTs during cutting CNT polycarbonate composites (CNT/PC) and evaluate the impact of recycling CNT/PC (up to 20 cycles) on the emission during cutting operation. Methods: Cutting CNT/PC bars was conducted using a saw with a diamond coated blade at 1600 rpm in an enclosing chamber. Particle number concentration and size distribution emitted from cutting were measured using real time instruments: a fast mobility particle sizer and an aerodynamic mobility particle sizer. Particles were also collected using an electrostatic precipitator and examined by a transmission electron microscope for particle morphology. Result: After saw's motor background correction, cutting of CNT/PC released airborne nanoparticles with geometric mean of particle concentrations from 4.01 × 10 4  to 1.47 × 10 5 particles/cm 3, but we did not find the effect of recycling CNT/PC on nanoparticle emission during cutting operation. The count median diameter of particles varied from 21 to 24 nm. Free CNTs were not observed during cutting CNT/PC; however, particles with extruding fibres or CNTs, and respirable fibres were found. Discussion: Our findings were consistent with several studies which investigated and characterised airborne particles generated from cutting CNT composites. Although free CNTs were not observed, we did find particles with CNTs embedded in the PC matrix, particles with CNTs or fibre extrusions, and respirable fibres produced during cutting CNT/PC. The health risk and hazard profile of these particles is limited and need for future research. In the meanwhile, exposure controls should be implemented during finishing CNT composites.